2018
DOI: 10.1212/wnl.0000000000005005
|View full text |Cite
|
Sign up to set email alerts
|

Neurofilament light protein in blood predicts regional atrophy in Huntington disease

Abstract: ObjectiveNeurofilament light (NfL) protein in blood plasma has been proposed as a prognostic biomarker of neurodegeneration in a number of conditions, including Huntington disease (HD). This study investigates the regional distribution of NfL-associated neural pathology in HD gene expansion carriers.MethodsWe examined associations between NfL measured in plasma and regionally specific atrophy in cross-sectional (n = 198) and longitudinal (n = 177) data in HD gene expansion carriers from the international multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 22 publications
4
60
0
4
Order By: Relevance
“…Plasma NfL also correlated with rates of brain atrophy and cognitive decline in HD patients and may predict disease onset in premanifest HD mutation carriers (Byrne et al, 2017). A recent report also demonstrated that plasma NfL predicts regional atrophy in the HD brain, suggesting that, with further development and regulatory validation, this may be a useful peripheral biomarker for future HD clinical trials (Johnson et al, 2018).…”
Section: Biomarkers Of Target Engagementmentioning
confidence: 87%
“…Plasma NfL also correlated with rates of brain atrophy and cognitive decline in HD patients and may predict disease onset in premanifest HD mutation carriers (Byrne et al, 2017). A recent report also demonstrated that plasma NfL predicts regional atrophy in the HD brain, suggesting that, with further development and regulatory validation, this may be a useful peripheral biomarker for future HD clinical trials (Johnson et al, 2018).…”
Section: Biomarkers Of Target Engagementmentioning
confidence: 87%
“…As such, imaging biomarkers may play a role as our ability to quantify macrostructural and microstructural damage (Figure 3 ). Serum and CSF biomarkers of “brain damage,” such as ultrasensitive detection of neurofilament protein, have been developed as a surrogate marker for clinical trials in neuroinflammatory and neurodegenerative diseases ( 146 ). Thus the rapid progress in our understanding of both pathophysiology and biomarkers of neurolupus is providing a much-needed roadmap to advance the field.…”
Section: Future Directionsmentioning
confidence: 99%
“…NFL enrichment in axons and its presence in synapses suggest that axonal injury and synaptic/neuronal death occurring in several neurodegenerative/neurological disorders may result in increased cerebrospinal fluid (CSF) NFL concentrations. Thus, increased body fluid NFL levels have been suggested to indicate neuroaxonal and white matter degeneration [4,5].…”
Section: Introductionmentioning
confidence: 99%